(untitled) (Albayan Scientific Journal, 2023)
Usually the state intervenes in economic policies in various forms, and the effects of these policies may be unclear through their impact on income or achieving productive or economic efficiency. Matrix Policy Analysis is one of the tools for assessing and analyzing policies, where the prices of social of agricultural crops were compared with private prices to estimate the elements of the Policy Analysis Matrix for wheat crops by comparing social prices and private prices by adopting a mathematical method known as (Policy Analysis Matrix).The production inputs were divided into local inputs and tradable inputs, and estimate the need of each one hectare from each production factor by using social and private prices after adopting the world exchange for the local currency, which estimated by 1.57 dinars / dollars in order to adjust the world prices of the inputs and outputs. The results of the study indicated that the positive value of the net policy transfers amounted about 222.37 dinars per tonne, which means that the policies came in the interest of the producers in the short term, as the rest of the results indicated the existence of government support for output prices and the existence of financial subsidies through the purchase of production inputs at a lower price comparing with world prices. As well as the existence of government support on local inputs and not imposing taxes on their use, as the negative value of social prices indicated that the state bears the loss by imposing a price lower than its real value, and the study recommended the need to continue providing direct and indirect support to determine a fair price for the supply of wheat crops. In proportion to the global price before the cultivation the crop in order to include the product covering the costs, achieving a reasonable profit margin and a fair price for consumers, promising to consider government policies, as well as continuing to produce wheat despite the non-comparative advantage in its production because it is one of the important strategic crops related to food security also recommended the adoption of methods of analysis that take into account a comparison of local prices with world prices to study the extent of agricultural systems response to price intervention policies and the efficiency of the performance of those policies.